Development of ImmTOR Tolerogenic Nanoparticles for the Mitigation of Anti-drug Antibodies - Kishimoto, Takashi Kei (Frontiers in Immunology, 2020)
The development of anti-drug antibodies (ADAs) is a common cause for treatment failure and hypersensitivity reactions for many biologics. The focus of this review is the development of ImmTOR, platform technology designed to prevent the formation of ADAs that can be applied broadly across a wide variety of biologics by inducing immunological tolerance with ImmTOR nanoparticles encapsulating rapamycin. The induction of tolerance is antigen-specific and dependent on the incorporation of rapamycin in nanoparticles and the presence of the antigen at the time of administration of ImmTOR. Evidence for the induction of specific immune tolerance versus general immune suppression is supported by the findings that: 1) ImmTOR induces regulatory T cells specific to the co-administered antigen; 2) tolerance can be transferred by adoptive transfer of splenocytes from treated animals to naïve recipients; 3) the tolerance is durable to subsequent challenge with antigen alone; and 4) animals tolerized to a specific antigen are capable of responding to an unrelated antigen. ImmTOR nanoparticles can be added to new or existing biologics without the need to modify or reformulate the biologic drug. The ability of ImmTOR to mitigate the formation of ADAs has been demonstrated for coagulation factor VIII in a mouse model of hemophilia A, an anti-TNF monoclonal antibody in a mouse model of inflammatory arthritis, pegylated uricase in hyperuricemic mice and in nonhuman primates, acid alpha-glucosidase in a mouse model of Pompe disease, recombinant immunotoxin in a mouse model of mesothelioma, and adeno-associated vectors in a model of repeat dosing of gene therapy vectors in mice and in nonhuman primates. Human proof-of concept for the mitigation of ADAs has been demonstrated with SEL-212, a combination product consisting of ImmTOR + pegadricase, a highly immunogenic enzyme therapy for the treatment of gout. ImmTOR represents a promising approach to preventing the formation of ADAs to a broad range of biologic drugs.